Equilibrium configuration of sandy embayed beaches from the Southwest Portuguese rocky coast - Gama, C. (2020)
The planform of five embayed sandy beaches (São Torpes, Furnas, Amoreira, Monte Clérigo and Arrifana), from the Southwest Portuguese rocky coast were compared to theoretical equilibrium curves (logarithmic spiral and parabolic). The beach planform configurations were defined based on aerial photography and the 2 m (MSL) contour extracted from DGPS field surveys (Furnas and Amoreira beaches). In order to analyse beaches morphodynamic, the volumetric active sediment changes, wave climate characteristics and wave propagation effects to nearshore were characterized. The wave breaking height and beach configuration is responsible for different degrees of exposure to the dominant NW wave direction. Major volumetric changes were largely associated with storm incidence. Comparison between real beach planform and predicted static equilibrium configurations suggests that the Arrifana beach represents a perfect example of a fully developed parabolic bay shape while, the other four beaches are not represented by any theoretical curve approach. In fact, the 2 m (MSL) contour at the Amoreira beach describes a convex beach planform tendency. The effect of the wave direction over the diffraction point was tested but the results points to a low diffraction effect. The Furnas beach revealed a high width variation at the northern extreme related with a more energetic wave climate, dominant from West, with lower diffraction. This study shows that the studied beaches presents a complex dynamic equilibrium that is a function of the subaerial beach configuration, the intertidal bar system variation, the degree of exposure to the dominant NW wave direction and the storm incidence.